A Comparative Study of Over-Current Sensing for Traction Inverters. (21st January 2021) - Niu, He
Abstract : The over-current condition for a traction inverter can indicate flaws on control algorithms, interference on logic signals, hardware aging, or hardware misconduct. Thus, proper detection of over-current conditions during inverter operation is a critical item for inverter development and product validation. This paper reviews several widely used over-current detection methods and a few theoretically approved over-current detection methods. The main focus of this review includes the sensing bandwidth, sensing accuracy, and implementation complexity of the studied over-current detection methods. The advantages of those widely used methods and the application requirements for the theoretically and prototypingly approved methods are concluded by this review.